Leading Commodities for Food Subsectors - Istiqomah Dunggio; Suharno Suharno; Nia Rosiana (Universitas Gorontalo, 2023)
Based on constant prices, the agricultural sector's GRDP growth rate trends to decline between 2018 and 2020. Given the various commodities that have been developed in Gorontalo Regency's agricultural sector, particularly in the food sub-sector, it is hoped that there will soon be superior commodities that are well developed and can positively affect the region's economic growth, particularly in the agricultural sector, particularly in the food sub-sector. The goal of this study was to use LQ (Location Quotient) and SSA (Shift Share Analysis) analysis tools to identify basic and non-basic commodities in the food sub-sector of Gorontalo Regency, identify commodities belonging to progressive growth, and identify the leading commodities in the food sub-sector of Gorontalo Regency. According to the analysis's findings, rice, corn, and soybeans were the three most important fundamental commodities in the Gorontalo Regency's food sub-sector. Corn, rice, and soybeans were among the agricultural products in the Gorontalo Regency that were categorized as having advanced or progressive development. According to the findings of the LQ and SSA analysis summarized, corn, rice, and soybeans are the top three commodities in the Gorontalo Regency